Model Intervensi Konseling Islami bagi Kesehatan Mental Peserta Didik pada Sekolah Islam dan Pesantren - Risabella Nuriyanah Burhani; Zainal Arifin (TADARUS, 2026)
Mental health challenges among students in Islamic schools and pesantren have become increasingly significant due to the combined pressures of academic demands, social expectations, and spiritual obligations. Existing literature indicates a rise in stress, anxiety, and emotional instability, yet counselling practices in many Islamic educational settings remain intuitive, unstandardized, and insufficiently aligned with contemporary psychological frameworks. This article aims to map current Islamic counselling interventions implemented within educational institutions and to develop an integrative theoretical model that responds to the psychological–spiritual needs of learners. Utilizing a narrative review approach, this study synthesizes research published in the past five years across Google Scholar, DOAJ, SINTA, and Scopus, focusing on interventions grounded in Islamic principles and applied within schools, madrasahs, and pesantren. Findings show that existing approaches such as Qur’anic therapy, Prophetic counselling, Sufi-based methods, and Islamic–CBT hybrids largely emphasize spiritual–affective dimensions but lack methodological coherence and structured evaluation. The article proposes the TAUHID-CARE Framework as its core theoretical contribution, integrating tazkiyah awareness, adaptive cognition, unity of self, heart-centred emotion regulation, Islamic behavioural activation, divine connection, and counsellor roles oriented toward accompaniment, advisement, regulation, and education. This framework represents the study’s novelty, offering a tauhid-based and pedagogically relevant model. The review concludes the need for more systematic, evidence-informed approaches to strengthen Islamic counselling in educational contexts.